Development of an Integrated Raw Material Inventory Management Information System with a Food Menu for Profit and Loss Calculation Using the Rapid Application Development (RAD) Method (Case Study: Bento Kopi Pamulang) - Dalia Oktaviyanti; Wasis Haryono (Yayasan Lembaga Studi Makwa, 2025)
The use of information technology is a crucial factor in improving business efficiency, particularly in inventory management. Bento Kopi Pamulang still relies on manual recording of raw material inventory, which leads to various challenges such as data errors, information delays, and inaccurate COGS calculations. To address these challenges, this study developed a digital-based inventory management information system integrated with food menu data. The development was conducted using the Rapid Application Development (RAD) method, encompassing planning, design, prototype development, and implementation. Each stage was conducted iteratively with direct user involvement, from needs interviews and design validation to prototype trials and implementation evaluation. Active user involvement helped ensure the system met operational needs in the field. The resulting system was proven capable of recording raw material inflows and outflows in real time, automatically calculating COGS, and presenting faster and more accurate financial reports. System testing showed a 40% increase in recording efficiency and up to 95% increase in data accuracy compared to the manual system. Abstrak Pemanfaatan teknologi informasi menjadi faktor penting dalam meningkatkan efisiensi bisnis, terutama pada aspek pengelolaan persediaan. Bento Kopi Pamulang masih mengandalkan pencatatan manual untuk stok bahan baku, yang menyebabkan berbagai kendala seperti kesalahan data, keterlambatan informasi, dan perhitungan HPP yang tidak akurat. Untuk menjawab permasalahan tersebut, penelitian ini mengembangkan sistem informasi manajemen inventory berbasis digital yang terintegrasi dengan data menu makanan. Pengembangan dilakukan menggunakan metode Rapid Application Development (RAD), yang mencakup tahap perencanaan, desain, pengembangan prototipe, dan implementasi. Setiap tahap dilakukan secara iteratif dengan keterlibatan langsung dari pengguna, mulai dari wawancara kebutuhan, validasi desain, uji coba prototipe, hingga evaluasi implementasi. Keterlibatan aktif pengguna membantu memastikan sistem sesuai dengan kebutuhan operasional di lapangan. Sistem yang dihasilkan terbukti mampu mencatat keluar masuk bahan baku secara real-time, menghitung HPP secara otomatis, serta menyajikan laporan keuangan yang lebih cepat dan akurat. Pengujian sistem menunjukkan adanya peningkatan efisiensi waktu pencatatan sebesar 40%, dan akurasi data meningkat hingga 95% dibanding sistem manual.